2014
DOI: 10.1039/c4cc01924e
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the antibiotic tropodithietic acid by the marine bacterium Phaeobacter inhibens

Abstract: The biosynthesis of tropodithietic acid was investigated using a combinatorial approach of feeding experiments, gene knockouts and bioinformatic analyses. The mechanism of sulfur introduction is distinct from known mechanisms in holomycin, thiomarinol A and gliotoxin biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(125 citation statements)
references
References 21 publications
3
122
0
Order By: Relevance
“…For both cases, these HFCD enzymes are predicted to catalyze key biosynthetic oxidative sulfur transformations. 36, 37 …”
Section: Resultsmentioning
confidence: 99%
“…For both cases, these HFCD enzymes are predicted to catalyze key biosynthetic oxidative sulfur transformations. 36, 37 …”
Section: Resultsmentioning
confidence: 99%
“…The biosynthetic pathway of TDA has not been fully elucidated (Brock, Nikolay & Dickschat, 2014). Both labelling (Cane, Wu & Van Epp, 1992; Thiel et al, 2010) and genetic dissection (Geng & Belas, 2010) studies have shown that its aromatic skeleton is derived from phenylacetyl-CoA produced by the shikimate pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[12,30] Besides the already known occurrence in P. gallaeciensis CIP 105210, tropone was also found in Phaeobacter sp.I8.25 and Loktanellak oreensis II 4.36.…”
Section: Other Compoundsmentioning
confidence: 94%